08 | Monitoring chronic diseases and risk stratification through clinical data repository in the Local Health Authority of Enna - V. Calabrese; M. C. Burgio; P. La Paglia; A. Di Pasquale; L. Gritti; N. La Grotteria; R. Miserendino; M. Zappia; A. Allotta; A. Cristaldi; V. Restivo; S. Scondotto (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. Chronic diseases represent a major public health priority due to population ageing and the increasing burden of multimorbidity. Reliable tools for estimating disease prevalence and stratifying the population are essential to plan health assistance level, according to the objectives of the Italian National Chronicity Plan. The Clinical Data Repository (called Banca Dati Assistiti, BDA) is a valuable resource for population health management and the implementation of community-based care pathways. Materials and Methods. A descriptive observational study was conducted involving people residents in the Local Health Authority (LHU) of Enna during the period 2022–2024. Data were extracted from the local BDA, which integrates datafrom hospital discharge records, pharmaceutical databases, exemption registries, patients anagraphis, and mortality register. Chronic conditions were identified and patients classified using algorithms inspired by the Chronic Related Groups (CReG) model. The prevalence of chronic diseases and their distribution by age group and health district were analysed. Results. A total of 56,912 individuals were identified as having at least one chronic condition, corresponding to a prevalence of 37.5% among residents in LHU of Enna. Differences among health districts were observed, due to variations in the age structure of the resident people. Analysis by diagnostic subgroup showed a marked concentration of patients in a limited number of highly prevalent conditions, hypertension (15.5%), hypercholesterolaemia (10.0%), type 2 diabetes mellitus (7.5%), and chronic obstructive pulmonary disease (COPD). Population stratification revealed that approximately two-thirds of patients belonged to low healthcare-needs categories. Conclusions. Approximately one-third of people residents in Enna were managed by the National Health Service for at least one chronic condition. The adoption of clinical data repository tools represents a key strategy to improve the accuracy of supplying care and ensure the sustainability of healthcare systems.